Community-Managed Educational Institutions (From Perdikan to Pesantren: An Examination of the Legacy of Interfaith Community Educational Institutions) - Ach. Kholili; Muhammad Ihsan; Maimun (al-Afkar, Journal For Islamic Studies, 2025)
This study explores the history of perdikan as the precursor of pesantren in Indonesia. Perdikan was initially an autonomous region serving as a center of education based on local wisdom. However, the process of Islamization transformed perdikan into a formal religious educational institution, known as pesantren. This research employs a library research method to analyze this transformation.The findings reveal that Islamization brought significant changes to the educational system in perdikan, shifting its focus from local customs to Islamic teachings. Pesantren later evolved into centers of moral, social, and economic education, playing a crucial role in the dissemination of Islam and community development. Moreover, pesantren demonstrated remarkable adaptability to modern demands, integrating contemporary curricula without losing their traditional values.